An Improved Sensorless Control Strategy of Ship IPMSM at Full Speed Range - Zhang, Zhenrui; Guo, Haohao; Liu, Yancheng; Zhang, Qiaofen; Zhu, Pengli; Iqbal, Rashid (IEEE access, 2019)
This paper proposed an improved sensorless control strategy for ship electric propulsion which bases on I/f control and back electromotive force integral (EMF), suppressing the speed fluctuation during algorithm switching, improving the flux estimation accuracy of internal permanent magnet synchronous motors (IPMSMs) and achieving the stable operation of the motor. Firstly, this strategy was adopted for controlling the stator current during the switching process to improve speed fluctuation. Then, a simple flux estimation method is presented by rewriting the mathematical model of IPMSM. To achieve the result which overcomes the problem of flux estimation and current measurement errors and improved LPF was developed which solved the phase delay and DC-offset problem of flux estimation. Finally, the propeller load platform is under construction to verify the effectiveness of the control strategy. Experimental results show that the system based on this method works smoothly and it has better speed tracking performance.